Urgensi Penerapan Sistem Ekonomi Islam - Fahrurrozi, Fahrurrozi (El-Barka, 2019)
Abstract: The ideology of capitalism cannot be separated from the understanding of European liberalism that occurred in the 18th century, where capitalism and liberalism were born in response to the dictatorship of the feudal lords and the church at that time. Meanwhile, the emergence of socialism in the 19th century, could not be separated from the role of Karl Marx who wrote a book The Communist Manifesto of a German socialist figure who had contributed in the revival of the union and unity of the workers and intellectuals who had more than a century been amputated by market mechanisms. The Islamic economic system regulates all economic activities, so that humans as economic agents cannot be free as freely as possible, there are limits set in the Koran and Hadith, all the objectives of economic activity cannot be separated from Islamic values, making and selling illicit goods such as alcohol is not permissible in Islamic economics. The Islamic economic system is not only used as an alternative economic system but is a solution of various economic problems today. Ø§Ù„Ù…Ù„Ø®Øµ: Ù„Ø§ ÙŠÙ…ÙƒÙ† ÙØµÙ„ Ø£ÙŠØ¯ÙŠÙˆÙ„ÙˆØ¬ÙŠØ© Ø§Ù„Ø±Ø£Ø³Ù…Ø§Ù„ÙŠØ© Ø¹Ù† Ù…ÙÙ‡ÙˆÙ… Ø§Ù„Ù„ÙŠØ¨Ø±Ø§Ù„ÙŠØ© Ø§Ù„Ø£ÙˆØ±ÙˆØ¨ÙŠØ© Ø§Ù„ØªÙŠ ØØ¯Ø«Øª ÙÙŠ Ø§Ù„Ù‚Ø±Ù† 18. Ù„Ù‚Ø¯ ÙˆÙ„Ø¯Øª Ø§Ù„Ø±Ø£Ø³Ù…Ø§Ù„ÙŠØ© ÙˆØ§Ù„Ù„ÙŠØ¨Ø±Ø§Ù„ÙŠØ© Ø§Ø³ØªØ¬Ø§Ø¨Ø©Ù‹ Ù„Ø¯ÙŠÙƒØªØ§ØªÙˆØ±ÙŠØ© Ø§Ù„Ù„ÙˆØ±Ø¯Ø§Øª Ø§Ù„Ø¥Ù‚Ø·Ø§Ø¹ÙŠØ© ÙˆØ§Ù„ÙƒÙ†ÙŠØ³Ø© ÙÙŠ Ø°Ù„Ùƒ Ø§Ù„ÙˆÙ‚Øª. ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø£Ø«Ù†Ø§Ø¡ØŒ Ù„Ø§ ÙŠÙ…ÙƒÙ† ÙØµÙ„ Ø¸Ù‡ÙˆØ± Ø§Ù„Ø§Ø´ØªØ±Ø§ÙƒÙŠØ© ÙÙŠ Ø§Ù„Ù‚Ø±Ù† 19 Ø¹Ù† Ø¯ÙˆØ± ÙƒØ§Ø±Ù„ Ù…Ø§Ø±ÙƒØ³ Ø§Ù„Ø°ÙŠ ÙƒØªØ¨ ÙƒØªØ§Ø¨Ù‹Ø§ Ø¨Ø¹Ù†ÙˆØ§Ù† Ø§Ù„Ø¨ÙŠØ§Ù† Ø§Ù„Ø´ÙŠÙˆØ¹ÙŠ Ù„Ø´Ø®ØµÙŠØ© Ø§Ø´ØªØ±Ø§ÙƒÙŠØ© Ø£Ù„Ù…Ø§Ù†ÙŠØ© Ø³Ø§Ù‡Ù… ÙÙŠ Ø¥ØÙŠØ§Ø¡ Ø§ØªØØ§Ø¯ ÙˆÙˆØØ¯Ø© Ø§Ù„Ø¹Ù…Ø§Ù„ ÙˆØ§Ù„Ù…ÙÙƒØ±ÙŠÙ† Ø§Ù„Ø°ÙŠÙ† ØªÙ… Ø¨ØªØ±Ù‡Ù… Ø¨ÙˆØ§Ø³Ø·Ø© Ø¢Ù„ÙŠØ§Øª Ø§Ù„Ø³ÙˆÙ‚ Ù…Ù†Ø° Ø£ÙƒØ«Ø± Ù…Ù† Ù‚Ø±Ù†. ÙŠÙ†Ø¸Ù… Ø§Ù„Ù†Ø¸Ø§Ù… Ø§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ Ø¬Ù…ÙŠØ¹ Ø§Ù„Ø£Ù†Ø´Ø·Ø© Ø§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠØ©ØŒ Ø¨ØÙŠØ« Ù„Ø§ ÙŠÙ…ÙƒÙ† Ù„Ù„Ø¨Ø´Ø± Ø¨ÙˆØµÙÙ‡Ù… Ø¹Ù…Ù„Ø§Ø¡ Ø§Ù‚ØªØµØ§Ø¯ÙŠÙŠÙ† Ø£Ù† ÙŠØªÙ…ØªØ¹ÙˆØ§ Ø¨Ø§Ù„ØØ±ÙŠØ© Ù‚Ø¯Ø± Ø§Ù„Ø¥Ù…ÙƒØ§Ù†ØŒ ÙÙ‡Ù†Ø§Ùƒ ØØ¯ÙˆØ¯ Ù…ØØ¯Ø¯Ø© ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† ÙˆØ§Ù„ØØ¯ÙŠØ«ØŒ ÙˆÙ„Ø§ ÙŠÙ…ÙƒÙ† ÙØµÙ„ Ø¬Ù…ÙŠØ¹ Ø£Ù‡Ø¯Ø§Ù Ø§Ù„Ù†Ø´Ø§Ø· Ø§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠ Ø¹Ù† Ø§Ù„Ù‚ÙŠÙ… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©ØŒ Ù„Ø§ ÙŠØ¬ÙˆØ² ØµÙ†Ø¹ ÙˆØ¨ÙŠØ¹ Ø³Ù„Ø¹ ØºÙŠØ± Ù…Ø´Ø±ÙˆØ¹Ø© Ù…Ø«Ù„ Ø§Ù„ÙƒØÙˆÙ„ ÙÙŠ Ø§Ù„Ø§Ù‚ØªØµØ§Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ. Ù„Ø§ ÙŠØªÙ… Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù†Ø¸Ø§Ù… Ø§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ ÙƒÙ†Ø¸Ø§Ù… Ø§Ù‚ØªØµØ§Ø¯ÙŠ Ø¨Ø¯ÙŠÙ„ ÙØØ³Ø¨ØŒ Ø¨Ù„ Ù‡Ùˆ ØÙ„ Ù„Ù…Ø´Ø§ÙƒÙ„ Ø§Ù‚ØªØµØ§Ø¯ÙŠØ© Ù…Ø®ØªÙ„ÙØ© Ø§Ù„ÙŠÙˆÙ…. Abstrak: Ideologi kapitalisme tidak bisa dipisahkan dari paham liberalisme eropa yang terjadi pada abad ke 18, dimana kapitalisme dan liberalisme lahir sebagai respon atas diktatorisme para kaum feodal dan gereja waktu itu. Sementara itu kemunculan sosialisme pada abad ke 19, tidak lepas dari peranan Karl Marx yang menulis sebuah buku The Communist manifesto seorang tokoh sosialis Jerman yang telah memberikan sumbangsih dalam kebangkitan persatuan dan kesatuan kalangan buruh dan intelektual yang sudah lebih dari seabad diamputasi oleh mekanisme pasar. Sistem ekonomi Islam mengatur seluruh aktifitas ekonomi, sehingga manusia sebagai pelaku ekonomi tidak bisa bebas sebebas-bebasnya, ada batasan-batasan yang sudah diatur dalam al-Qur’an dan Hadits, seluruh tujuan aktifitas ekonomi tidak bisa di pisahkan dengan nilai-nilai Islam, membuat dan menjual barang-barang haram seperti alcohol tidak diperbolehkan dalam ekonomi Islam. Sistem ekonomi Islam bukan hanya dijadikan sebagai sistem ekonomi alternate tapi menjadi solusi dari berbagai permasalahan ekonomi saat ini.